2010
DOI: 10.1016/j.bpj.2010.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Dynamics of Rat Basophilic Leukemia Immunoglobulin E Receptors (FcɛRI) on Planar Ligand-Presenting Surfaces

Abstract: There is considerable interest in the signaling mechanisms of immunoreceptors, especially when triggered with membrane-bound ligands. We have quantified the spatiotemporal dynamics of the redistribution of immunoglobulin E-loaded receptors (IgE-FcepsilonRI) on rat basophilic leukemia-2H3 mast cells in contact with fluid and gel-phase membranes displaying ligands for immunoglobulin E, using total internal reflection fluorescence microscopy. To clearly separate the kinetics of receptor redistribution from cell s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 46 publications
3
34
0
Order By: Relevance
“…The IgE-FceRI diffusivity in clusters is similar to that of the monomeric, uncrosslinked IgE-FceRI [14,24]. The average cluster radius hRi was 206 nm (Â/1.36), which is consistent with the microscopically observable cluster size and previous measurements [8]. IgE-FceRI receptor complexes confined within central patches of apparent average radius hRi = 503 nm (Â/1.45) diffused faster than expected, with an average diffusivity of hDi = 0.17 lm 2 /s (Â/1.7).…”
Section: Ige-fceri Receptors Diffuse Fastest In Central Patchessupporting
confidence: 88%
See 2 more Smart Citations
“…The IgE-FceRI diffusivity in clusters is similar to that of the monomeric, uncrosslinked IgE-FceRI [14,24]. The average cluster radius hRi was 206 nm (Â/1.36), which is consistent with the microscopically observable cluster size and previous measurements [8]. IgE-FceRI receptor complexes confined within central patches of apparent average radius hRi = 503 nm (Â/1.45) diffused faster than expected, with an average diffusivity of hDi = 0.17 lm 2 /s (Â/1.7).…”
Section: Ige-fceri Receptors Diffuse Fastest In Central Patchessupporting
confidence: 88%
“…2 shows the average diffusion coefficient (solid black line) for IgE-FceRI receptor complexes diffusing within central patches (circles) and clusters (squares). The average diffusivity of clusters (triangles) was hDi = 3.3 Â 10 À3 lm 2 /s (Â/2.1), significantly smaller than IgE-FceRI diffusivity and within previously reported observations [8]. Clusters tracked in this experiment did not show evidence of directed motion (as has been previously reported [8]); however, the tracking time was shorter in this study, making detection of directed motion more difficult.…”
Section: Ige-fceri Receptors Diffuse Fastest In Central Patchessupporting
confidence: 87%
See 1 more Smart Citation
“…It is complex to separate these processes in the data analysis. Therefore, Spendier et al (2010) use a micropipette to initiate cell contact with a functionalized substrate resulting in a large initial contact site. A micropipette can exert high enough forces to press the cell against the substrate (Hocde et al, 2009).…”
Section: Conclusion and Discussion -Alcam And Cd6mentioning
confidence: 99%
“…Studies include effects of D 2 O on tobacco seed growth (Lewis, 1934), IgE-Mediated histamine release from human leukocytes (Gillespie and Lichtenstein, 1972), actin filament velocities (Chaen et al, 2001), protein flexibility (Cioni and Strambini, 2002), human pancreatic tumor cells (Hartmann et al, 2005), phospholipid membranes (Beranova et al, 2012), kinesin-1 gliding assay (Maloney et al, 2014), and stabilization of tubulin as observed previously in microtubule gliding assays (Panda et al, 2000) and in biochemical experiments on isolated tubulin proteins from beef brain (Houston et al, 1974) and goat brain (Das et al, 2008). Microtubules are polarized polymers of α/β tubulin heterodimers and undergo alternating phases of growth and shrinkage with sudden transitions between the two (Bartolini et al, 2005 In this paper we use the RBL-2H3 cell line, a typical mast cell model system (Thomas et al, 1992;Posner et al, 1995;Carroll-Portillo et al, 2010;Spendier et al, 2010), to start investigating this question. Mast cells are immune cells that originate from the bone marrow and circulate in an immature form in the body until they settle in tissue and mucosal surfaces, where they mature.…”
mentioning
confidence: 99%